Stimulation of Variant Forms of the Mitochondrial DNA Helicase Twinkle by the Mitochondrial Single-Stranded DNA-Binding Protein - Rodrigues, Ana P. C. [UNESP]; Oliveira, Marcos T. [UNESP] (Springer Nature, 2021)
Defects in mitochondrial DNA (mtDNA) maintenance may lead to disturbances in mitochondrial homeostasis and energy production in eukaryotic cells, causing diseases. During mtDNA replication, the mitochondrial single-stranded DNA-binding protein (mtSSB) stabilizes and protects the exposed single-stranded mtDNA from nucleolysis; perhaps more importantly, it appears to coordinate the actions of both the replicative mtDNA helicase Twinkle and DNA polymerase gamma at the replication fork. Here, we describe a helicase stimulation protocol to test in vitro the functional interaction between mtSSB and variant forms of Twinkle. We show for the first time that the C-terminal tail of Twinkle is important for such an interaction, and that it negatively regulates helicase unwinding activity in a salt-dependent manner.
Keywords: dsDNA unwinding assay; Mitochondrial DNA replication; mtSSB; P66; Twinkle